Allenes in Diels–Alder Cycloadditions - Hopf, Henning; Sherburn, Michael S. (Synthesis, 2021)
For a long time, allenes—and cumulenic systems in general—played a relatively minor role in Diels–Alder cycloadditions. This situation has changed, since allenes are more readily available and as their unique stereochemical features in [4+2]cycloadditions are more widely recognized. This review presents a comprehensive overview of allenes in Diels–Alder processes using selected examples. Allenes in dienes, dienophiles and cycloadducts are covered, inter- and intramolecular Diels–Alder cycloadditions are discussed, and stereochemical features of the addition process are described. Areas of emerging importance are also covered, including allenic components in dehydro-Diels–Alder processes, and dendralenic allenes in Diels–Alder sequences for the rapid generation of target-relevant molecular complexity. Preparatively useful methods for allenic precursor synthesis are also discussed.1 Introduction2 Allenic Dienes2.1 Vinylallenes2.2 Bisallenes2.3 Cross-conjugated Allenes3 Allenic Dienophiles4 Intramolecular Diels–Alder Cycloadditions5 Allenic Cycloadducts6 Conclusions and Outlook
Keywords: Diels–Alder addition; allenes as dienes and dienophiles; intermolecular cycloaddition; intramolecular cycloaddition; stereoselective synthesis; dehydro-Diels–Alder reactions; rapid generation of molecular complexity